WITH GRC AS A MODERATING VARIABLE, HOW DOES COMPANY SIZE AND AGE AFFECT FIRM VALUE? - Sula Yosege Sembiring Kembaren; Gunardi Endro (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Public companies aim to increase the firm’s value because it is the primary indicator by investors in considering their decisions. The increase in the company's value attracts potential investors because the company's value is identical to the shareholders' welfare. This study examines the effect of firm size and age on firm value with GRC as moderating. The population uses companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. Data collection using the purposive sampling method obtained 376 samples. Secondary data in the form of annual reports and financial reports. This study uses GRC as a moderator of the relationship between firm size and age on firm value. The analysis technique used is Moderated Regression Analysis (MRA). The analytical tool used in SPSS 26 with multiple linear regression testing. The results showed that the size and age of the company partially and simultaneously can affect the firm’s value. The GRC variable can be a moderator that strengthens the interaction between company size and age on a firm’s value. Companies listed on the IDX should carefully consider complementing the GRC component because it can strengthen competitive advantages such as company size and age, thereby increasing the firm’s value.